PELATIHAN PEMANFAATAN MICROSOFT EXCEL DALAM PENYUSUNAN LAPORAN KEUANGAN MAHASANTRI PONDOK PESANTREN GRIYA SANTRI MAHABBAH - ani, fenty febri (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
Technological developments in the digital era influence various aspects of life in Indonesia, including the financial management of students at the Griya Santri Mahabbah Islamic Boarding School. Preparing accurate financial reports has become important, and advances in computerization, especially Microsoft Excel, have made significant contributions to this effort. This training aims to provide training to students regarding using Microsoft Excel in making financial reports and effective cash management. Training methods include lectures, discussions, and questions and answers. The material presented includes the use of Ms. Excel in financial reports and cash management for mahasantri is easily practiced. Participants succeeded in understanding the material and were able to identify the differences between recording cash receipts and cash disbursements. They can also group transactions by date within each month to monitor money coming in and out each month.